Visualizing Authentic Data and Supporting Learning about Weather, Climate, and Seasons with Colorful Weather Trackers - Lottero-Perdue, Pamela (Innovations in Science Teacher Education, 2024)
In fall 2023, I designed a means for the pre-service teachers (PSTs) in my Earth-Space Science class to engage with authentic data and co-construct data visualizations—weather trackers—to enable them to track daily temperature and precipitation data over time. I did so to support their data literacy, data visualization literacy, and abilities to analyze and interpret data, make sense of patterns, and make evidence-based arguments about climate and seasonal temperature differences. We examined weather in three locations: our local area and two mystery locations. Each location had one weather tracker for daily maximum temperature and one for daily total precipitation. Most weeks of the semester, the PSTs spent about 15 minutes knotting a piece of yarn to each tracker for each day of the preceding week, according to data reports from the National Weather Service and National Oceanic and Atmospheric Administration (NOAA). We used a key whereby certain colors of yarn corresponded to certain temperature and precipitation ranges. Throughout the semester, PSTs reflected the data displayed on the trackers. Ultimately, PSTs were able to make arguments about the probable designated climate zones and relative latitudes for the two mystery locations. In this paper, I share the design and implementation of the weather trackers, how my students and I grappled with messy authentic data, and how the weather tracker data visualizations contributed to PSTs’ sensemaking about climate and seasons.